Multifunctional pH‐Responsive Gelatin/Agarose Hydrogels Incorporating Gum Arabic for Wound Repair - Z. Ghasemi; K. Mohagheghiyan; M. Kharaziha; M. Shokri; S. M. Ahmadi Tafti (Advanced Healthcare Materials, 2026)
ABSTRACT This study aims to develop pH‐sensitive GelAgar‐GA hydrogels composed of Gum Arabic (GA)‐incorporated gelatin and agarose for wound healing applications. Our results reveal that the agarose content modulates the structural, chemical, physical, and biological properties of hydrogels. Noticeably, the hydrogel containing 3 wt% agarose (GelAgar‐GA‐3) shows optimized characteristics, including superior elastic modulus (186 ± 12 kPa) and tensile strength (173 ± 12 kPa), mimicking the mechanical properties of native skin. The swelling ability of this hydrogel is modulated via pH changes. Noticeably, the water absorption capacity of GelAgar‐GA‐3 at pH = 5 is 247 ± 47%, which increases to 327±45% at pH = 9. GelAgar‐GA hydrogels also indicate significant coagulation ability, low hemolysis (